2009
DOI: 10.1002/jor.21032
|View full text |Cite
|
Sign up to set email alerts
|

Repair of large osteochondral defects in rabbits using porous hydroxyapatite/collagen (HAp/Col) and fibroblast growth factor‐2 (FGF‐2)

Abstract: Articular cartilage has a limited capacity for self-renewal. This article reports the development of a porous hydroxyapatite/ collagen (HAp/Col) scaffold as a bone void filler and a vehicle for drug administration. The scaffold consists of HAp nanocrystals and type I atelocollagen. The purpose of this study was to investigate the efficacy of porous HAp/Col impregnated with FGF-2 to repair large osteochondral defects in a rabbit model. Ninety-six cylindrical osteochondral defects 5 mm in diameter and 5 mm in de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
105
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(111 citation statements)
references
References 37 publications
5
105
0
1
Order By: Relevance
“…The subchondral bone formation may have resulted from osteoconductive property of nanocomposite BC-HA activated with BMP-2. This is in conjunction with previous reports 5,47,48 where subchondral bone formation is reported to enhance regeneration of the articular cartilage. In the current in vivo study, the size of the modified BC scaffold was significantly reduced at 3 months, indicating biodegradative resorption and integration in the surrounding tissue.…”
supporting
confidence: 92%
“…The subchondral bone formation may have resulted from osteoconductive property of nanocomposite BC-HA activated with BMP-2. This is in conjunction with previous reports 5,47,48 where subchondral bone formation is reported to enhance regeneration of the articular cartilage. In the current in vivo study, the size of the modified BC scaffold was significantly reduced at 3 months, indicating biodegradative resorption and integration in the surrounding tissue.…”
supporting
confidence: 92%
“…In contrast, hypocellularity was observed in the cell-free scaffolds and there was no obvious cell orientation. Regarding fibrocartilage development, positive collagen type I staining was not observed to the same extent in the cell-seeded scaffold, suggesting fibrocartilage formation in 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 the cell-free scaffold and hyaline-like cartilage formation in the cell-seeded scaffold, echoing the observations of Maehara 14 Nonetheless, analysis with a modified O'Driscoll scoring system, revealed that there was no statistical difference observed between the cell-free scaffold and the cell-seeded scaffold (Table 2) other cartilage repair studies using a cell-free PEOT scaffold, these results compare well with Jansen, 6 where cartilage repair was not observed frequently, while bone repair and integration with native tissue was observed. In contrast, the cell-seeded PEOT/PBT scaffold in this study appeared to augment cartilage repair in addition to bone repair, with higher O'Driscoll scores for percentage hyaline cartilage, surface continuity, tidemark and thickness of repair tissue compared to the cell-free scaffolds (Fig.…”
Section: Discussionsupporting
confidence: 56%
“…Tissue engineered bone and clinical translation revealed the most abundant member utilised within bone tissue engineering strategies in vivo was FGF-2, also known as basic FGF (Hirata et al, 2013;Hong et al, 2010;Maehara et al, 2009;Shirakata et al, 2010).…”
Section: Fgfmentioning
confidence: 99%
“…Considering related fold increases in bone formation within large (1.3 to 3 fold Shirakata et al, 2010)) and small animals (1.1 to 16.4 fold (Goodman et al, 2003;Hong et al, 2010)), it is interesting to note that higher dosages correlated with greater fold increases (defects with highest fold increase included tibial fracture and calvarial defect respective to large and small animals). Evidently, data suggest positive correlation between FGF-2 treatment and bone formation, potentially due to induced vessel ingrowth and ossification at the defect site (Guo et al, 2006;Maehara et al, 2009 (Bland et al, 1995;Dunstan et al, 1999;Kelpke et al, 2004), and one study utilised FGF-18 (Carli et al, 2012) which has been shown to promote chondrogenesis amongst many other functions. FGF-1 was administered between 3 and 7 µg in small animals including mouse (Dunstan et al, 1999), rabbit (Bland et al, 1995) and rat (Kelpke et al, 2004).…”
Section: Direct Administration Of Fgfmentioning
confidence: 99%